Bridging the gap: the roles of social capital and ethnicity in medical student achievement. Issue 1 (January 2015) - Vaughan, Suzanne; Sanders, Tom; Crossley, Nick; O'Neill, Paul; Wass, Val
<x xml:space="preserve">Abstract</x> Objectives Within medical education, there is a discrepancy between the achievement level of White students and that of their ethnic minority peers. The processes underlying this disparity have not been adequately investigated or explained. This study utilises social network analysis to investigate the impact of relationships on medical student achievement by ethnicity, specifically by examining homophily (the tendency to interact with others in the same group) by ethnicity, age and role. Methods Data from a cross‐sectional social network study conducted in one UK medical school are presented and are analysed alongside examination records obtained from the medical school. Participants were sampled across the four hospital placement sites; a total of 158 medical students in their clinical phase (Years 3 and 4) completed the survey. The research was designed and analysed using social capital theory. Results Although significant patterns of ethnic and religious homophily emerged, no link was found between these factors and achievement. Interacting with problem‐based learning (PBL) group peers in study‐related activities, and having seniors in a wider academic support network were directly linked to better achievement. Students in higher academic quartiles were more likely to be named by members of their PBL group in study activities and to name at least one tutor or clinician in their network. Students from lower‐achieving groups were least likely to have the social capital enabling, and resulting from, interactions with members of more expert social groups. Conclusions Lower levels of the social capital that mediates interaction with peers, tutors and clinicians may be the cause of underperformance by ethnic minority students. Because of ethnic homophily, minority students may be cut off from potential and actual resources that facilitate learning and achievement.